Maladaptive changes in multiple traits caused by fishing: impediments to population recovery - Walsh, Matthew R; Munch, Stephan B; Chiba, Susumu; Conover, David O (Ecology letters, 2006)
Some overharvested fish populations fail to recover even after considerable reductions in fishing pressure. The reasons are unclear but may involve genetic changes in life history traits that are detrimental to population growth when natural environmental factors prevail. We empirically modelled this process by subjecting populations of a harvested marine fish, the Atlantic silverside, to experimental size-biased fishing regimes over five generations and then measured correlated responses across multiple traits. Populations where large fish were selectively harvested (as in most fisheries) displayed substantial declines in fecundity, egg volume, larval size at hatch, larval viability, larval growth rates, food consumption rate and conversion efficiency, vertebral number, and willingness to forage. These genetically based changes in numerous traits generally reduce the capacity for population recovery.